The dynamic triage interplay of Hsp90 with its chaperone cycle and client binding - Xiaozhan Qu; Simin Wang; Shuo Zhao; Chanjuan Wan; Weiya Xu; Chengdong Huang (Nature Communications)
Abstract Hsp90, a crucial molecular chaperone, regulates diverse client proteins, impacting both normal biology and disease. Central to its function is its conformational plasticity, driven by ATPase activity and client interactions. However, comprehensive insights into Hsp90’s dynamic molecular transitions remain elusive. Using solution NMR spectroscopy, we reveal how ATP binding, hydrolysis, and client engagement drive conformational and dynamic shifts in E. coli Hsp90, HtpG, through its chaperone cycle. Pronounced conformational fluctuations occur, especially in regions crucial for nucleotide binding and conformational transitions. ATP binding induces slow-exchanging conformations, representing discrete on-path transition states from open to closed forms, while ATP hydrolysis shifts HtpG into a compact conformation. Client binding acts as an allosteric switch, dynamically priming HtpG for elevated chaperone activity and, therefore, its efficient remodeling. Here, we provide atomic-level insights into Hsp90’s functional mechanism, highlighting the interplay of conformation, dynamics, nucleotide, and client interactions.